Penyisipan Pesan Tersembunyi Dalam Citra Menggunakan Metode Spread Spectrum dan Least Significant Bit(LSB) - Indrawan, Muhammad Caesar Gilang; Kadyanan, I Gusti Agung Gede Arya; Supriana, I Wayan; Widiartha, I Made (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2025)
The advancement of information technology has facilitated data transmission but also increased cybersecurity threats. To protect data security, steganography is used to hide messages within images, ensuring only the intended recipient can read them. This research uses two steganography methods: Spread Spectrum and Least Significant Bit (LSB). The advantage of the Spread Spectrum method is that it produces images with low PSNR and MSE values, making the steganographic images similar to the original ones. However, the embedding and extraction processes are slow. To overcome this weakness, the LSB method is used, allowing for quick message embedding and extraction while maintaining the resolution and size of the images before and after message embedding. In this study, Spread Spectrum is used to determine the location of message embedding, while LSB is used for the message embedding process.